(untitled) (ҚазҰУ Хабаршысы. География сериясы, 2023)
The movement of air particles is a very mobile medium, which is usually chaotic or turbulent in nature. Turbulence (translated from latin "turbo" means vortex) is a state of the atmosphere in which a vortex and wind can form horizontal and vertical cracks. The influence of atmospheric turbulence on the flight of the aircraft is manifested in sudden and unexpected changes in the horizontal flight configuration. A sharp and sudden change in flight mode due to the effect of turbulence is usually called a "vibration" or bump. Vibration depends on the physical state of the atmosphere, time of year, time of day, altitude of the terrain, its orographic features and meteorological conditions. In the article, work was carried out to identify the features of vibration propagation and its relationship with meteorological parameters at the airport of Almaty in the period from 2015 to 2019. As a result, it was showed that the maximum frequency of vibration at the considered standard levels of 960-110 hPa corresponds to the cold period of the year and occurs at the height of takeoff and landing. As for the connection between air temperature and vibration, it has found that vibration is most common in the temperature range from -4 ° C to 0 ° C. It was also revealed that the frequency of vibration most often coincides in cloudless conditions, i.e. the total number of cases is 439 (00 hours) and 609 (12 hours), respectively, the frequency is 61 and 84%. During the study of the relationship between vibration and clouds, it was recorded that vibration exists only with 3 different clouds, i.e. Ci, Ac and Sc. The results of the study can be widely used in the fields of civil aviation, military aviation.